Cellular Recovery and Therapeutic Rechallenge After Cancer Therapy-Induced Kidney Injury: Mechanistic Insights and Clinical Implications - Yosuke Dotsu; Kazumasa Akagi; Noritaka Honda; Midori Matsuo; Hirokazu Taniguchi; Shinnosuke Takemoto; Tomoya Nishino; Hiroshi Mukae (Cells, 2026)
Cancer therapy-related acute kidney injury has become an increasingly common challenge as modern treatments prolong survival and increase exposure to potentially nephrotoxic therapies. Decisions regarding therapeutic rechallenge have relied on normalizing serum creatinine and recovering estimated glomerular filtration rate, despite growing evidence that biochemical recovery does not necessarily indicate restoration of kidney integrity or resilience. In this review, we propose biological kidney recovery as a conceptual framework that integrates mechanisms of kidney injury and repair (adaptive and maladaptive) with emerging biomarkers and therapeutic rechallenge. We first summarize the distinct mechanisms of kidney injury induced by platinum-based chemotherapy, immune checkpoint inhibitors, and vascular endothelial growth factor pathway inhibitors, highlighting how these differences influence subsequent repair. We then discuss the cellular and metabolic processes underlying adaptive repair, the transition to maladaptive remodeling, and current approaches for assessing biological recovery through pathology, biomarkers, and multi-omics technologies. Finally, we present a practical framework for individualized therapeutic rechallenge based on an integrated assessment of kidney-, tumor-, and patient-related factors and outline future directions for precision onco-nephrology. By shifting the focus from filtration alone to biological recovery, this framework enables more informed therapeutic rechallenge aimed at preserving both oncologic efficacy and long-term kidney health.